Aligning web services with the semantic web to create a global read-write graph of data - Lanthaler, Markus; Guetl, Christian (IEEE Computer Society, 2011)
Despite significant research and development efforts, the vision of the Semantic Web yielding to a Web of Data has not yet become reality. Even though initiatives such as Linking Open Data gained traction recently, the Web of Data is still clearly outpaced by the growth of the traditional, document-based Web. Instead of releasing data in the form of RDF, many publishers choose to publish their data in the form of Web services. The reasons for this are manifold. Given that RESTful Web services closely resemble the document-based Web, they are not only perceived as less complex and disruptive, but also provide read-write interfaces to the underlying data. In contrast, the current Semantic Web is essentially read-only which clearly inhibits networking effects and engagement of the crowd. On the other hand, the prevalent use of proprietary schemas to represent the data published by Web services inhibits generic browsers or crawlers to access and understand this data; the consequence are islandsof data instead of a global graph of data forming the envisioned Semantic Web. We thus propose a novel approach to integrate Web services into the Web of Data by introducing an algorithmto translate SPARQL queries to HTTP requests. The aim is to create a global read-write graph of data and to standardize the mashup development process. We try to keep the approach as familiar and simple as possible to lower the entry barrier and foster the adoption of our approach. Thus, we based our proposal on SEREDASj, a semantic description language for RESTful data services, for making proprietary JSON service schemas accessible.